Avaliação do perfil lipídico em pacientes com doença inflamatória intestinal - Adorne, Elaine de Fatima (2016)
Introduction: The association betweenchangesin lipid metabolismand chronicinflammatory bowel diseasesis not well established. It is observed thatinflammatory markers which arepresent inCrohn's disease (CD) and inulcerative colitis(UC) are also presentin metabolicsituationsthat are characterized byatherogenicdyslipidemia. It ispossible to assumethat changes inlipid profilemay be associated withchronic inflammation,potentiallyaggravating theclinical situationand increasing the riskof cardiovascular diseases. Aim: This research aims to investigate the associationbetween patients’ lipidprofile who areunderinflammatory bowel disease andtheactivity levelsof chronicinflammatory disease. Method: Cross-sectional studyof patients who are followedin the Inflammatory Bowel Disease(IBD)clinic ofSão LucasHospital atPontifíciaUniversidadeCatólicado Rio Grande do Sul. We have evaluateddemographic and anthropometric data,andbiochemicaltests (C-reactive protein, erythrocyte sedimentation rate, blood count andlipid profile). Patientswere classified accordingto the severity ofCrohn's diseaseregarding Harvey-Bradshaw index forinflammatory activity; in relation toulcerative colitis, the classification followedthe severity ofacuteoutbreakaccording toTrueloveandWitts. Results:The study involved 122 patients of both genders who are under chronic inflammatory bowel disease. The patients were divided into two groups: Crohn's disease (n = 64; 52.5%) and ulcerative colitis (n = 58; 47.5%). Their average age is 41.6 around 12.6 years and their body mass index(BMI) is 25 around 4.4 kg/m2. Concerning the laboratory markers which were evaluated, we have found that LDL-c was higher in UC when compared to LDL-c CD (110.0 +35.8 x 91.3±33.1 mg/dL; p= 0.006). Regarding Harvey-Bradshaw indexforinflammatory activity, 63.8% of CD patients have had mild disease activity and CRP was the only marker in correlation to the disease severity (p = 0. 027). In UC, the distribution of patients according to Truelove and Witts index showed that 63.2% of patients have had mild disease; while for markers lipid, HDL-c levels (p = 0.036) and total cholesterol (p = 0.028) were correlated to the disease severity. HDL-c was the only lipoproteins that have presented, in 67.6% of the sample,valuesbelow those recommended by the Brazilian Society of Cardiology. Conclusion:We have concludedthat in IBDpatients, it is clear that theLDL-cissignificantly higherinUC. TheHDL-c,in both diseases,has presentedlevels below recommended. Among CDpatients, those who werein moresevere inflammatorysituationhave presented significantlyhigher levelsof CRP whencomparedto UCpatients. In relation totheseverity of the disease, which is determinedbyHarvey-Bradshaw indexorCDandTrueloveandWittsforUC, patients from both groups havebehavedsimilarly.